PENGARUH EKSTRAK DAUN THE HIJAU (CAMELLIA SINENSIS) PADA PEMBUATAN NAGET DAGING SAPI TERHADAP DAYA AWET - Faiqoh, Areza Febriyanti (Jurnal Peternakan Nusantara, 2020)
Green tea (Camellia sinensis) contains active compounds in the form of polyphenols which can function as natural preservatives for food products as nuggets. This study was conducted to study the effect of using green tea leaf extract on the process of making beef nuggets for shelf life (total number of bacteria, rancidity and early spoilage), and determine the best concentration of green tea leaf extract which can produce the best preservation of beef nuggets. This research was conducted at the Animal Product Processing Technology Laboratory (TPPP), Faculty of Animal Husbandry and Test Service Laboratory, Faculty of Agricultural Industrial Technology, Padjadjaran University on March 2019. This research was conducted experimentally using a Randomized Complete Design with the utilization of green tea leaf extract in 0, 0.5, 1, and 1.5%, the measured variable is the total number of bacteria, rancidity and early spoilage. The results showed that the addition of green tea leaf extract 0,5% (P2), 1% (P3), and 1,5% (P4) had a significant effect (P<0,05) on the total number of bacteria, value of rancidity and time of early spoilage compared to 0% (P1). Addition of green tea leaf extract in 1.5% to beef nuggets gave the best results for the shelf life of beef nuggets with the total number of bacteria 99.71 × 105 CFU/g, the value of rancidity 0.53 mg malonaldehyde/kg, and the time of early spoilage was 1061.20 minutes.Keywords :  green tea, Nuggets, total number of bacteria, rancidity, early spoilage